The regulation of tau phosphorylation by PCTAIRE 3: Implications for the pathogenesis of Alzheimer's disease - A.Z. Herskovits; P. Davies (Neurobiology of Disease, 2006)
In the course of Alzheimer's disease, phosphorylated tau aggregates to form paired helical filaments, highly ordered filamentous structures that accumulate within neurons and contribute to the formation of neurofibrillary tangles. This study examines the role of PCTAIRE 3, a cdc2 family protein kinase, within this disease process. We report an elevation in the protein levels of PCTAIRE 3 in the temporal cortex of AD relative to control brains. Analysis of paired helical filaments prepared from AD brain tissue indicates that PCTAIRE 3 is concentrated within this pathological material. Overexpression of PCTAIRE 3 in cell culture suggests that the protein acts indirectly to stimulate phosphorylation at the pT231 and pS235 sites on tau, residues that are modified early in the process of AD pathogenesis. The resurgence of cell cycle proteins is an important mechanism in Alzheimer's disease (AD), and we propose that PCTAIRE 3 is a PHF-associated kinase that modulates tau phosphorylation.